Tumor-to-Tumor Metastasis to Chromophobe Renal Cell Carcinoma: A First Report - Toshitaka Shin; Tomoko Kan; Fuminori Sato; Hiromitsu Mimata (Case Reports in Urology)
Tumor-to-tumor metastasis is a rare phenomenon. From our review of the international literature, around 150 cases have been reported since it was first documented by Campbel in 1868. Renal clear cell carcinoma is well known to be the most common recipient of tumor-to-tumor metastasis in all tumors. However, renal chromophobe cell carcinoma has not been reported to be a recipient. Here, we report a first case of colorectal carcinoma metastatic to chromophobe renal cell carcinoma.